1993
DOI: 10.1111/j.1528-1157.1993.tb02584.x
|View full text |Cite
|
Sign up to set email alerts
|

Manganese and Epilepsy: Brain Glutamine Synthetase and Liver Arginase Activities in Genetically Epilepsy Prone and Chronically Seizured Rats

Abstract: Low blood manganese (Mn2+) concentration is associated with epilepsy in humans and rats. The low Mn2+ concentration is attributed by some investigators to the seizure activity associated with the epilepsy, whereas others propose that the low Mn2+ concentration may be secondary to genetic mechanisms underlying the epilepsy. To begin to differentiate between these possibilities, Mn(2+)-binding enzymes of liver and brain (i.e., arginase and glutamine synthetase, respectively) were assayed in rats exposed to chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…The high intakes of Mn did not affect glutamine synthetase activity in the brain or seizure occurrence. Nonetheless, Liang et al (2012) 61 supported the findings of Carl et al 68 when they examined the role of Mn deficiency in inducing epilepsy in mice. Animals with low MnSOD activity exhibited increased risk for epileptic seizures that was attributed to oxidative stress, with subsequent mitochondrial dysfunction.…”
Section: Deficienciessupporting
confidence: 82%
See 1 more Smart Citation
“…The high intakes of Mn did not affect glutamine synthetase activity in the brain or seizure occurrence. Nonetheless, Liang et al (2012) 61 supported the findings of Carl et al 68 when they examined the role of Mn deficiency in inducing epilepsy in mice. Animals with low MnSOD activity exhibited increased risk for epileptic seizures that was attributed to oxidative stress, with subsequent mitochondrial dysfunction.…”
Section: Deficienciessupporting
confidence: 82%
“…It is conceivable that Mn is related to epileptic seizures by affecting arginase activity in the liver. 68 In contrast, Critchfield and others 69 investigated the effect of Mn supplementation on seizure development in the offspring of two groups of pregnant mice fed 45 (control) and 1000 mg Mn g À1 diet, respectively. The high intakes of Mn did not affect glutamine synthetase activity in the brain or seizure occurrence.…”
Section: Deficienciesmentioning
confidence: 93%
“…Mn is necessary for a variety of metabolic functions, including lipid, protein, and carbohydrate metabolism, and it serves as a cofactor for various enzymes, including the antioxidant enzyme superoxide dismutase (SOD), as well as enzymes involved in neurotransmitter synthesis and metabolism (Carl et al 1993; Keen et al 2000; Johnson and Giulivi 2005; Aschner et al 2007). However, exposure to high levels of Mn may lead to a neurological disorder that shares many similarities with Parkinson’s disease (PD), and is referred to as manganism.…”
Section: Introductionmentioning
confidence: 99%
“…Another manganoprotein is mitochondrial superoxide dismutase (Keen et al, 1984). Mn deficiency and the ensuing low Mn concentration in the blood are known to be associated with epilepsy in both humans and experimental animals (Carl et al, 1993). Moreover, Mn ions may be involved in the processes dynamically coupled to the electrophysiological activity of neuronal axons; we demonstrated that Mn is released with neurotransmitters into the extracellular space during stimulation with high K Ï© (Takeda et al, 1998d).…”
Section: Introductionmentioning
confidence: 88%